Balance impairment limits ability to increase walking speed in individuals with chronic stroke. Issue 5 (27th February 2017) - Middleton, Addie; Braun, Carty H.; Lewek, Michael D.; Fritz, Stacy L.
Abstract: Purpose Determine the relationship between balance impairments and the ability to increase walking speed (WS) on demand in individuals with chronic stroke.Methods WS and Berg Balance Scale (BBS) data were collected on 124 individuals with chronic stroke (>6 months). The ability to increase WS on demand (walking speed reserve, WSR) was quantified as the difference between participants' self-selected (SSWS) and maximal (MWS) walking speeds. Correlation, regression and receiver operating characteristic (ROC) analyses were performed to investigate the relationship between balance and the ability to increase WS.Results Of sample, 58.9% were unable to increase WS on demand (WSR < 0.2 m/s). BBS scores were associated with WSR values ( r s =0.74, 0.65–0.81) and were predictive of 'able/unable' to increase WS [odds ratio (OR) = 0.75, 0.67–0.84]. The AUC for the ROC curve constructed to assess the accuracy of BBS to discriminate between able/unable to increase WS was 0.85 (0.78–0.92). A BBS cutscore of 47 points was identified [sensitivity: 72.6%, specificity: 90.2%, +likelihood ratio (LR): 7.41, −LR: 0.30].Conclusions The inability to increase WS on demand is common in individuals with chronic stroke, and balance appears to be a significant contributor to this difficulty. A BBS cutscore of 47 points can identify individuals who may benefit from balance interventions to improve the ability to increase their WS. Implications for Rehabilitation: A majority of individuals with chronic stroke may be unable to increase their walking speed beyond their self-selected speed on demand. This may limit functional ambulation, as these individuals are walking "at capacity". Balance impairments contribute to the inability to increase walking speed. A Berg Balance Scale score <47 points can be used to identify individuals with chronic stroke walking "at capacity" due to balance impairments.